Sustainable asset management on decision making factors of building retrofitting - Mohamad Adzizulrohim Abd Malek,; Azlan Shah Ali,; Mohamad Rizal Baharum,; Noraishikin Zulkarnain, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper presents the significant factors considered during decision making in retrofitting process of public ownership such as hospital and school buildings. One of the major issues in facility planning is to retrofit the existing facility. In fact, for government assets, they have to be economically managed by knowing the holding cost, so that it is viable to be retained in long run. The objectives of this paper are to list down the entire decision making factors that considered in asset decision making. The aim of this paper is to propose the innovative model that will become a framework or guideline as to improve and as an added value to the existing procedure. This model will also consider some adaptation from the existing model that has been implemented by our countries. The results expected that could be used by organizations especially for the decision makers as a guideline or a tool to make a wise and good decision in building replacement related activities.